Effectiveness of physical activity interventions in improving objective and patient-reported outcomes in head and neck cancer survivors: A systematic review. (June 2021) - Lynch, Patrick T.; Horani, Sami; Lee, Rebecca; Sumer, Baran D.; Lee, Simon C.; Mayo, Helen G.; Rethorst, Chad; Day, Andrew T.
Highlights: Physical activity interventions in HNC survivors often confer some benefit. The impact of physical activity interventions on HNC survival is unknown. Both conventional and alternative physical activity interventions improve outcomes. Yoga and Tai Chi physical activity interventions frequently benefitted HNC survivors. Abstract: Objective: To assess the effectiveness of physical activity interventions in improving objective and patient-reported outcomes in HNC survivors. Introduction: Multiple guidelines recommend that head and neck cancer (HNC) survivors participate in regular physical activity. Physical activity is associated with improved outcomes and mortality in healthy individuals as well as in certain cancer populations. However, the effectiveness of physical activity interventions in HNC survivors is inadequately understood. Methods and results: Our literature search through December 2018 identified 2, 392 articles. After de-duplication, title and abstract review, full-text review and bibliographic search, 20 studies met all inclusion criteria. Inclusion criteria included any full-body physical activity intervention in HNC survivors that did not target discrete organ sites or functions (e.g. swallowing). Study cohorts included 749 predominantly male participants with a mean age range of 48–63 years. At their conclusion, physical activity interventions were associated with at least one significant improvement in an objective or patient-reported outcome in 75% of studies. Aerobic capacity and fatigue were the most commonly improved outcomes. None of the included studies evaluated associations with survival or recurrence. Although traditional aerobic and resistance interventions were more common, a greater proportion of alternative physical activity (yoga and Tai Chi) interventions demonstrated improved objective and patient-reported outcomes. Conclusion: Physical activity interventions in HNC survivors often conferred some improvement in objective and patient-reported outcomes. Additional highly-powered, randomized controlled studies are needed to establish the optimal type, intensity, and timing of physical activity interventions as well as their impact on oncologic outcomes.